RELAÇÕES ENTRE ÉTICA E EDUCAÇÃO AMBIENTAL: PERSPECTIVAS DE EDUCADORES AMBIENTAIS NO ENSINO SUPERIOR - Leandro, Luiz Alberto de Lima (2005)
Nowadays, most world conferences and contemporary writings on the subject, assure us that Society is passing through unprecedented environmental crises. Several authors present the problem as being caused by a crisis in ethics. As a solution comes the idea that only by means of action in the field of education will it be possible to visualize an appropriate answer to these environmental questions. Environmental literature suggests that Universities are the right places in which to work on society's problems. This document presents a proposal for reflection on Environmental Ethics for those educators who work in universities. It also suggests the importance of this reflection for the academic education of teachers and students, and in addition suggests the usefulness of creating an ethical code for this process. By examining the literature on the subject, it was possible, by means of shedding light on the concept of Ethics and environmental Ethics, to mark a trajectory through Philosophy and to investigate more profoundly Environmental Education in general, and more specifically the Environmental Education taught at universities. The methodology used qualitative research. When it was created, it was used to analyze categories of data which had come from research participants; the participants agreed that the ethical question was an essential way of finding solutions to environmental problems. The principal confusion on the ethical question is a conceptual one, and begs an immediate explanation. The reflection on Environmental Ethics did not facilitate, in general, any discussion on the interdisciplinary matter in the university environment. It concluded that the ethical education of students badly needed to be worked on. In order to permit universities to offer real valid alternatives, it is necessary to make institutional changes. The creation of an Ethical Code for environmental educators in universities remains both controversial and divisive.